PREDICTING THE POTENTIAL HABITAT AND DISTRIBUTION OF WESTERN TRAGOPAN (TRAGOPAN MELANOCEPHALUS) IN SELECTED AREAS OF AJ&K, PAKISTAN: A MAXENT MODELING APPROACH - H. Ali; U. Akram; S. Abbas; M. S. Ahmed; F. M. Qamer B. Khan; M. N. Awan; Z. Ali; A. A. Chaudhry; A. Saghir; M. Nagai (Journal of Animal and Plant Sciences, 2015)
Western Tragopan (Tragopan melanocephalus) is a beautiful pheasant species and is endemic to western Himalayas. It has large distribution range but different populations are fragmented within the western Himalayan moist temperate forests. Its distribution in Pakistan is restricted to some parts of Khyber Pakhtunkhwa and Azad Jammu & Kashmir (AJ&K).This species is globally ‘vulnerable’ since its fragmented small populations are declining due to continuing forest loss and habitat destruction throughout its range. This study was carried out to model the potential distribution and habitat of Western Tragopan in Neelam and Muzaffarabad districts of AJ&K by incorporating the physical, biological and climatic variables into MaxEnt model. L and cover data, Digital Elevation Model (DEM), slope, aspect, Normalized Difference Vegetation Index (NDVI), temperature, precipitation, topographic and sighting datasets were processed in Geographic Information System (GIS) to produce meaningful predictor variables, subsequently used in the MaxEnt software. The results showed that 11,112 ha area (2% of the total study area) is highly suitable for Western Tragopan, 30,248 ha area (5.3%) moderately suitable while 525,445 ha (92.7%) area is unsuitable. Jackknife test evaluated the importance of predictor variables and DEM, precipitation and land cover were found to be the most important variables for this study. The study evaluated the species-habitat relationship within the study area and can be helpful in the management and in-situ conservation planning of the species in its distribution range.
Keywords: Western Tragopan; Potential distribution; MaxEnt modeling; in-situ conservation